Optimization Techniques in Real Estate Investment Portfolios: A Quantitative Approach - Patel, Tarang; Singh, Pushpendra; Dhaakad, Deepak; Vaghela, Sidhraj; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R (Greenation International Journal of Engineering Science, 2023)
This study explores optimization techniques in real estate investment portfolios, focusing on balancing risk and return through diversification, sustainability, and technology integration. By analyzing responses from 104 participants across different demographic groups, the research examines how factors such as age, gender, education, and occupation influence the adoption of strategies like AI-driven decision-making, ESG considerations, and corporate governance. The findings reveal that while traditional optimization techniques remain essential, there is growing acceptance of advanced tools and sustainable practices. The study emphasizes the importance of a holistic approach to portfolio management, combining financial performance with ethical and environmental considerations. Future research can further investigate emerging technologies and global regulatory impacts on real estate investments.